Influence Leadership, Technology and Digital Transformation towards Implementation Strategy Culture Organization - Mutmainnah, Audy Zalfa; Ali, Hapzi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The Effect of Leadership, Technology and Digital Transformation on the Implementation of Organizational Culture Strategy is a scientific article of literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of influence between variables that will be used in further research. The object of research on online libraries, Google Scholar, Mendeley and other academic online media. Research methods with library research sourced from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) Leadership affects the Implementation of Organizational Culture Strategy; 2) Technology influences the Implementation of Organizational Culture Strategy; and 3) Digital Transformation affects the Implementation of Organizational Culture Strategy.